Associations of polychlorinated biphenyls exposure with plasma glucose and diabetes in general Chinese population: The mediating effect of lipid peroxidation. (1st September 2022) - Tan, Qiyou; Wang, Mengyi; Yu, Linling; Liang, Ruyi; Liu, Wei; Dong, Chaoqian; Zhang, Yongfang; Li, Minjing; Ye, Zi; Wang, Bin; Zhou, Min; Chen, Weihong
Abstract: Polychlorinated biphenyls (PCBs) exposure has been related to the abnormal glucose metabolism and the risk of diabetes. However, the joint effects of various PCBs are uncertain and the potential mechanisms remain unclear. Our objectives were to evaluate the associations of serum PCBs with fasting plasma glucose (FPG) and the risk of diabetes among a general Chinese population, and to estimate the mediating effects of oxidative stress in the above associations. Serum levels of seven indicator-PCBs (PCB-28, 52, 101, 118, 138, 153, and 180) and FPG values were determined among 4498 subjects from the Wuhan-Zhuhai cohort. Oxidative DNA damage biomarker (urinary 8-hydroxy-2′-deoxyguanosine, 8-OHdG) and lipid peroxidation biomarker (urinary 8-isoprostane, 8-iso-PGF2α ) were also measured. Positive relationships of serum PCBs with FPG values as well as the risk of diabetes were observed. With each 1% increment in the natural log-transformed values of wet weight serum PCBs, FPG levels increased a 0.125% for PCB-52, 0.168% for PCB-118, 0.221% for PCB-138, 0.273% for PCB-153, and 0.379% for ΣPCB (the sum of seven PCBs). The adjusted odds ratios of diabetes associated with wet weight PCBs were 1.186 for PCB-52, 1.373 for PCB-118, 1.635 for PCB-153, and 1.456 for ΣPCB. The seven serum PCBs showed positive overall effect on the risk of diabetes. Elevated PCB-28, PCB-52, PCB-118, PCB-138, PCB-153, and ΣPCB were associated with the increased urinary 8-iso-PGF2α, which was positively related with FPG values. Furthermore, urinary 8-iso-PGF2α partially mediated the positive associations between PCBs and FPG values, with the mediated proportions ranged from 3.20 to 12.93%. In conclusion, our results suggested that serum PCBs were positively related with increased oxidative stress, FPG values, and the risk of diabetes among a general Chinese population. Serum PCBs mixture had positive overall effect on the risk of diabetes. Lipid peroxidation partly mediated the FPG elevation induced by PCB exposure. Graphical abstract: Image 1 Highlights: Serum PCB-52, 118, 138, and 153 and ∑PCB were positively associated with FPG levels. Serum PCB-52, 118, and 153 and ∑PCB were positively associated with risk of diabetes. PCBs mixture showed positive overall effect on the risk of diabetes. Increased serum PCBs were associated with elevated urinary 8-iso-PGF2α . Urinary 8-iso-PGF2α mediated the associations between serum PCBs and increased FPG.